Use integration by parts, twice. The first time, let u = x^2 and dv = e^x dx; the second time, let u = 2x and let dv = e^x dx.
First time:
∫x^2e^x dx = x^2e^x - ∫2xe^x dx
Second time:
x^2e^x - ∫2xe^x dx = x^2e^x - (2xe^x - ∫2e^x)
Simplify/take antiderivative:
x^2e^x - (2xe^x - ∫2e^x) = x^2e^x - 2xe^x +∫2e^x = x^2e^x - 2xe^x + 2e^x = (x^2 - 2x + 2)e^x.
Now evaluate from 0 to 1.
(1 - 2 + 2)e^1 - (0 - 0 + 2)e^0 = e - 2.
2007-05-06 10:35:18
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
[0, 1]â«x²e^x dx
Proceed with integration by parts: u=x², du=2x dx, v=e^x, dv = e^x dx.
x²e^x | [0, 1] - [0, 1]â«2xe^x dx
e - [0, 1]â«2xe^x
Integrate by parts again: u=2x, du=2 dx, v=e^x, dv=e^x dx.
e - (2xe^x | [0, 1] - [0, 1]â«2e^x dx)
e - 2e + [0, 1]â«2e^x dx
Integrating directly:
e - 2e + 2e^x | [0, 1]
e - 2e + 2e - 2
Simplifying:
e-2
2007-05-06 17:36:50
·
answer #2
·
answered by Pascal 7
·
0⤊
0⤋